Penambahan Nilai Estetik pada Produk Selendang Batik Pesisiran dengan Aplikasi Manipulating Fabric - Mursidah, Mursidah; Cahyo, Andri Nur; Dwirainaninsih, Yustiana; Rachdantia, Dheasari (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The application of manipulating fabrics to batik can create uniqueness and exclusivity to increase its value. The application of manipulating fabrics on batik can support the development or creation of custom made batik based on creativity to create batik fashion innovation. This can encourage the creation of new product designs to refresh the market. The application of manipulating fabrics to batik provides novelty value because it adds use value to the product. Adding use value to batik products can add to the superiority of the product, namely that apart from being beautiful it also has a certain physical appearance. It is important to develop batik to maintain its sustainability. Batik as a cultural heritage still needs to continue to be developed to be transformed to the younger generation. There are still younger generations who think batik is old fashioned clothing. Batik can be modified to suit current modern fashion trends so that the younger generation is even more enthusiastic about preserving it. One way that can be done is by applying manipulating fabric. The aim of this research is to produce a new product design with the idea of providing additional use value to coastal motif batik products by applying the technique of manipulating fabrics. The method used is qualitative research with a practice-based approach to the creative arts creation process (practice-led research). The result of this research is a batik shawl with fabric manipulation applications in the form of embroidery, slashing and smocking.